QuCCs: an experimental of quantum key distribution using quantum cryptography and communication simulator - Ahmad Zukarnain, Zuriati; Buhari, Abudhahir; Harun, Nur Ziadah; Khalid, Roszelinda (Institute for Mathematical Research, Universiti Putra Malaysia, 2019)
The applications of quantum information science move towards bigger and better dimensions for the next generation technology. In the field of quantum cryptography and quantum computation, the world already witnessed various groundbreaking tangible products and promising results. Quantum cryptography is one of the mature fields of quantum mechanics and the devices are already available in the markets. In order to reach the heights of digital cryptography, the current state of quantum cryptography is still under various researches. However, the complexity of quantum cryptography is high due to combination of hardware and software. The lack of effective simulation tool to design and analyze the quantum cryptography experiments delays the reaching distance of the success. Therefore, in this paper, a framework to achieve an effective single photon based quantum cryptography simulation tool is proposed. The limitations of a commercial photonic simulation tool based experiments are also highlighted. Finally, the ideas for achieving one-stop simulation package for quantum based secure key distribution experiments are discussed. The proposed modules of simulation framework have been analyzed from the programming perspective.